Mourning in separation: contributions of psychology to coping it (Research, Society and Development, 2023)
Marital separation is understood as a rupture of ties involving two people, bringing consequences for the couple and also for the children and family members, understanding the phenomenon of mourning in separation helps in the elaboration of effective intervention techniques for the treatment. The objective of the research is to present the theoretical concepts related to the subject and the contributions of Psychology in the treatment of mourning. The methodology used is a bibliographic review of articles found in banks and repositories of public articles and also books on the subject. Grief in separation is a subject still little researched by Psychology, compared to the fact that divorces and separations are increasing. Psychology has techniques for the treatment and intervention of mourning in separation, favoring the healthy elaboration of mourning. The approach to grief in separation for children and adolescents is more delicate and involves greater responsibility on the part of caregivers.